Predictive Performance of Echocardiographic Parameters for Cardiovascular Events Among Elderly Treated Hypertensive Patients - Chowdhury, E.; Jennings, G.; Dewar, E.; Wing, L.; Reid, Christopher (2016)
Background: Hypertension leads to cardiac structural and functional changes, commonly assessed by echocardiography. In this study, we assessed the predictive performance of different echocardiographic parameters including left ventricular hypertrophy (LVH) on future cardiovascular outcomes in elderly hypertensive patients without heart failure. Methods: Data from LVH substudy of the Second Australian National Blood Pressure trial were used. Echocardiograms were performed at entry into the study. Cardiovascular outcomes were identified over short term (median 4.2 years) and long term (median 10.9 years). LVH was defined using threshold values of LV mass (LVM) indexed to either body surface area (BSA) or height2.7 : >115/95g/m 2 (LVH-BSA 115/95) or ≥49/45g/m 2.7 (LVH-ht 49/45) in males/females, respectively, and ≥125g/m 2 (LVH-BSA125) or ≥51g/m 2.7 (LVH-ht 51) for both sexes. Results: In the 666 participants aged ≥65 years in this analysis, LVH prevalence at baseline was 33%–70% depending on definition; and after adjusting for potential risk factors, only LVH-BSA 115/95 predicted both short- and long-term cardiovascular outcomes. Participants having LVH-BSA 115/95(69%) at baseline had twice the risk of having any first cardiovascular event over the short term (hazard ratio, 95% confidence interval: 2.00, 1.12–3.57, P = 0.02) and any fatal cardiovascular events (2.11, 1.21–3.68, P = 0.01) over the longer term. Among other echocardiographic parameters, LVM and LVM indexed to either BSA or height 2.7 predicted cardiovascular events over both short and longer term. Conclusions: In elderly treated hypertensive patients without heart failure, determining LVH by echocardiography is highly dependent on the methodology adopted. LV H-BSA 115/95 is a reliable predictor of future cardiovascular outcomes in the elderly.